Получение асимметричных соматических гибридов в роде Medicago - Кучук, Н.В.; Шаховский, Л.М.; Воронин, В.В.; Глеба, Ю.Ю. (Биополимеры и клетка, 1991)
Получены асимметричные соматические гибриды между различными видами люцерны (Medicago Sp.). Регенерированы растения в гибридной комбинации М. sativa + M. varia. Мезофильные канамицин-устойчивые протопласты M. varia облучали гамма-лучами в дозе 300 Гp. У них выявлен ген устойчивости к канамицину. Отбор асимметричных соматических гибридов вели по устойчивости к канамицинсульфату. В комбинации М. borealis+M. Iupidina получены клеточные линии. Канамицинустойчивые каллусные протопласты М. Iitpulina облучали гамма-лучами в дозе 500 Fp. Одержані асиметричні соматичні гібриди між різними видами люцерни (Medicago sp.). Як донорів використовували канамінинстінкі протопласти М. varia і М. lupulina. У гібридній комбінації між M sativa та опроміненою (300 Гр) М. varia відібрано 13 канаміцинстійких клітинних клонів. У одного з них одержані рослини. Кількість хромосом гібриду складала 2n = 70–72, шо значно більше, ніж у обох батьків – 2n = 32. Зроблено припущення, що здатність до регенерації одержаних гібридів перейшла від опроміненого донора M. varia. У гібридній комбінації між М. borealis та опроміненою (500 Гр) М. lupulina відібрано вісім канаміцинстійких клітинних клонів. Аналіз активності неоміцинфоефотрансферази та рДНК за допомогою блот-гібридизації по Саузерну показав гібридну природу одержаних ліній в обох комбінаціях. Interspecific somatic hybrids of Medicago have been obtained by «gamma-fusion». Kanarnycin resistant plants of M. varia and kanamycin resistant callus line of M. lupulina were used as donors. M. sativa and Λί. borialis were used as recipients. After fusion of gamma-irradiated (300 Gy) mesophyll protoplasts of M. varia with those of M. sativa, 13 kanamycin resistant hybrid clones were selected. We could induce the formation plant regenerants from one of the clones. Chromosome number of regenerated plants was 70—72, thus differing from both the parents 2n = 32 and indicating asymmetric genome constitution. Since the recipient genotype of Af. sativa was deficient for shoot morphogenesis in culture, we think that transfer of the regeneration ability from M. varia to the hybrid takes place. After fusion of gamma-irradiated (500 Gy) callus protoplasts of AT. Iupulina with mesophyll ones of Af. borealis, 8 kanamycin resistant clones were selected. Biochemical analysis involved hybrids of both species combinations. Activity of NPTII is detectable in hybrid plants as well as callus clones. Analysis of ribosomal DNA of hybrids by Southern blot hybridization demonstrated the presence of speciesspecific rDNA fragments of both parents.